The Magicians : A Novel - Grossman, Lev (New York : Viking, 2009)
Haboring secret preoccupations with a magical land he read about in a childhood fantasy series, Quentin Coldwater is unexpectedly admitted into an exclusive college of magic and rigorously educated in modern sorcery.
aMap on lining papers.
Keywords: College students -- Fiction; College graduates -- Fiction; Magic -- Fiction; Fiction; Bildungsromans